JEP 2020
DOI: 10.7176/jep/11-8-02
|View full text |Cite
|
Sign up to set email alerts
|

Review of Self-Regulated Learning in Massive Open Online Course

Abstract: Over the last decade, much attention has been paid the effects of self-regulated learning (SRL) in massive open online courses (MOOCs). However, a systematic understanding of the topic is rather limited. This study drew a general outline of important factors affecting the SRL in MOOCs. The study summarizes two important SRL modes as the theoretical basis. Then, the study analyses the motivational, metacognitive and cognitive regulation strategies, and behavioural regulation strategies which affect SRL in MOOCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Nonetheless, students also reported that they adopted technical strategies to tackle the problems by using more dependable internet providers and other technical strategies. This is closely related to the behavioural and contextual regulation strategies proposed by Zhu et al (2020), in which students attempt to structure their study environment to prepare for their e-learning activities.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Nonetheless, students also reported that they adopted technical strategies to tackle the problems by using more dependable internet providers and other technical strategies. This is closely related to the behavioural and contextual regulation strategies proposed by Zhu et al (2020), in which students attempt to structure their study environment to prepare for their e-learning activities.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, Pintrich's (2000) model shares some similarities with Zimmerman's (2002) model as the four phases are overlapped by four different components: (1) cognition, (2) motivation, (3) behaviour, and (4) context. Summarizing these two models, Zhu et al (2020) established an SRL model that addresses the online learning context, particularly with regard to Massive Open Online Courses (MOOCs). They argue that there are three major regulation strategies that students undertake to regulate their online learning activities, as illustrated in Figure 1.…”
Section: Models and Theories Of Self-regulated Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-regulation is an important component of student learning, and involves setting goals and the thoughts, feelings, and actions required to achieve those goals (Cohen, 2012;Zapata-Cuervo et al, 2021). Online courses tend to require a higher degree of student self-regulation, especially when the online course is presented in an asynchronous format with no set lecture time (Wang, Shannon, & Ross, 2013;Zhu, Mustapha, & Gong, 2020). Online learning can also have a negative impact on collaborative activities and discussion quality between students when conducted in a virtual setting compared to in-person learning, thereby reducing both student engagement with the course material and a deeper comprehension of course concepts (Dumford & Miller, 2018).…”
Section: Introductionmentioning
confidence: 99%